EVALUASI SISTEM PENGENDALIAN INTERN PEMERINTAH ATAS PELAYANAN PERIZINAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU DAERAH PROVINSI SULAWESI UTARA - Rahman, Magfirah; Nangoi, Grace B.; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2020)
Government in carry out public services such as licensing service or other services not escape the chances of risks, such as fraud and maladministration, then to minimize this risks, it takes an integral system that can control the implementation of service. Government Internal Control System (GICS) implementation whole in the central government and local government. GICS has an important role in the implementation of services by government agencies. The purpose of research was to evaluate internal control on licensing service in the Investment and One Stop Integrated Service Office of North Sulawesi based of Government Regulation Number 60 of 2008 regarding Government Internal Control System (GICS) consists of five components; control environment, risk assessment, control activities, information and communication and monitoring activities. The type of research used qualitative descriptive method. Data were collected by observation, interviews and documentation. The results showed that component of control activities which is physical asset was not in accordance with Government Regulation Number 60 of 2008, this difference because the security of assets was not running well. For other components, such as control environment, risk assessment, information and communication and monitoring activities, evaluation results indicate it was in accordance with Government Regulation Number 60 of 2008.